Cleavage of functional IL-2 receptor alpha chain (CD25) from murine corneal and conjunctival epithelia by MMP-9 - Farley William J; Chuang Eliseu Y; Puthenparambil Larry M; Pham Sapa; Pangelinan Solherny B; Yoon Kyung-Chul; De Paiva Cintia S; Stern Michael E; Li De-Quan; Pflugfelder Stephen C (BMC, 2009)
Abstract Background IL-2 has classically been considered a cytokine that regulates T cell proliferation and differentiation, signaling through its heterotrimeric receptor (IL-2R) consisting of α (CD25), β (CD122), γ chains (CD132). Expression of IL-2R has also been detected in mucosal epithelial cells. Soluble IL-2Rα (CD25) has been reported as an inflammatory marker. We evaluated the expression of CD25 and CD122 in the ocular surface epithelium and investigated the mechanism of proteolytic cleavage of CD25 from these cells. Methods Desiccating stress (DS) was used as an inducer of matrix metalloproteinase 9 (MMP-9). DS was created by subjecting C57BL/6 and MMP-9 knockout (BKO) mice and their wild-type littermates (WT) mice to a low humidity and drafty environment for 5 days (DS5). A separate group of C57BL/6 mice was subjected to DS5 and treatment with topical 0.025% doxycycline, a MMP inhibitor, administered QID. The expression of CD25 and CD122 was evaluated in cryosections by dual-label laser scanning confocal microscopy. Western blot was used to measure relative levels of CD25 in epithelial lysates. Gelatinase activity was evaluated by in situ zymography. Soluble CD25 in tear fluid was measured by an immunobead assay. Results CD25 and CD122 were abundantly expressed in cornea (all layers) and conjunctiva epithelia (apical and subapical layers) in nonstressed control mice. After desiccating stress, we found that immunoreactivity to CD25, but not CD122, decreased by the ocular surface epithelia and concentration of soluble CD25 in tears increased as MMP-9 staining increased. CD25 was preserved in C57BL/6 mice topically treated with an MMP-9 inhibitor and in MMP-9 knock-out mice. MMP-9 treatment of human cultured corneal epithelial cells decreased levels of CD25 protein in a concentration dependent fashion. Conclusion Our results indicate that functional IL-2R is produced by the ocular surface epithelia and that CD25 is proteolytic cleaved to its soluble form by MMP-9, which increases in desiccating stress. These findings provide new insight into IL-2 signaling in mucosal epithelia.